Storied with land: ‘transitional justice’ on Indigenous lands - Murdock, Esme G. (Journal of global ethics, 2018)
Transitional justice is positioned as an emergent discourse to grapple with the aim, and subsequent practices, of moving societies mired in violent political relations to more stable, democratic political relations. Increasingly, precepts of transitional justice are being applied to political reconciliatory processes in so-called liberal democratic states. This article examines limitations to transitional justice paradigms especially when applied to Indigenous-state reconciliatory processes by centering Indigenous scholarly discourse critical of both transitional justice and reconciliation processes that position Indigenous peoples, Indigenous lands, and the landed violence of colonialism as fixed in the past. The article offers an analysis of the limitations of neoliberal transitional justice and reconciliation processes that do not realize justice for Indigenous peoples and Indigenous lands by highlighting Indigenous-centered accounts of justice that promote collective capacities of Indigenous nations rooted in the ability of Indigenous peoples to experience themselves in the world in ways that center relations to land, world, and relatives (human and non-human).